Skeptical Theism, Moral Skepticism, and Divine Commands - Aikin, Scott (International journal for the study of skepticism, 2013)
Over the last twenty-five years skeptical theism has become one of the leading contemporary responses to the atheological argument from evil. However, more recently, some critics of skeptical theism have argued that the skeptical theists are in fact unwittingly committed to a malignant form of moral skepticism. Several skeptical theists have responded to this critique by appealing to divine commands as a bulwark against the alleged threat of moral skepticism. In this paper we argue that the skeptical theists’ appeal to divine commands fails to rescue their position from the threat of a worrisome form of moral skepticism.